2020
DOI: 10.1111/tri.13638
|View full text |Cite
|
Sign up to set email alerts
|

Stenting the ureteroneocystostomy reduces urological complications in kidney transplantation: a noninferiority randomized controlled trial, SPLINT trial

Abstract: The role of ureteral stents in living-donor kidney transplantation remains uncertain. In this randomized controlled trial (SPLINT), we compared urological complications in living-donor kidney transplantations performed with or without stents. We included 200 consecutive patients that received living-donor kidney transplantations at the Erasmus MC, University Medical Center, Rotterdam. Patients (124 males, 76 females, mean age 54 AE 13) were randomized for suprapubic externalized single J stents (N = 100) or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The use of ureteral stents could reduce urologic complications, including postoperative stenosis and leakage at the anastomotic site, as demonstrated by several case–control studies and randomized controlled trials [ 20 22 ]. However, prolonged stent retention might predispose to urinary tract infections, encrustations and blockade of stents [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ureteral stents could reduce urologic complications, including postoperative stenosis and leakage at the anastomotic site, as demonstrated by several case–control studies and randomized controlled trials [ 20 22 ]. However, prolonged stent retention might predispose to urinary tract infections, encrustations and blockade of stents [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to including the overall meta-analysis results of Mangus and Haag [1], we included all studies (with complete data) published since that report which were included in the more recent meta-analysis of Alberts et al [6] or more recent review by Wilson et al [24]. A recently reported randomized trial [25] was also included as well.…”
Section: Discussionmentioning
confidence: 99%
“…Percentages of urologic complications that developed post-transplant, as reported by other kidney transplant studies of extravesical ureteroneocystostomies, stratified by routine stent placement (yes/no), appear in Table 4 [1,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Our overall urologic complication incidence of 1.4% (7/500) is at least as good as every report (and better than most of the reports) shown in the table, including the 1.5% (6/407) incidence among Lich-Gregoir ureteroneocystostomies with routine stenting in 5 randomized trials combined as reported by Mangus and Haag [1].…”
Section: Comparing Our Percentage Who Developed a Urologic Complicatimentioning
confidence: 99%
“…Stenting the ureter during renal transplantation was a source of controversy for decades, and Ooms et al . [1] have grappled with this topic again in this issue of Transplant International. The team in Rotterdam have designed and implemented a research trial, after the first iteration of the Cochrane review on ureteric stents [2], published back in 2005.…”
mentioning
confidence: 99%